Analisis Putusan Mahkamah Konstitusi Terkait Politik Uang Berdasarkan Putusan Mahkamah Konstitusi Nomor 59/PUU-XXII/2024 - Pratama , Agung Gilang; Sadzali, Ahmad (Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This study is entitled “An Analysis of the Constitutional Court’s Decision on money politic Based on Constitutional Court Decision Number 59/PUU-XXII/2024.” The thesis addresses the following research questions: (1) What are the challenges in the regulation of money politic in Indonesia? (2) How do the Constitutional Court judges interpret money politic in Decision 59/PUU-XXII/2024 concerning the judicial review of Article 523, Paragraphs (1) and (2) of Law Number 7 of 2017 on General Elections? In addressing these questions, this study employs a qualitative descriptive research method, involving the classification and comparison of field data with legal theory to derive significant and scholarly conclusions. The research is conducted using normative and case study approaches. The findings indicate that the primary issues related to the first research question include structural challenges, insufficient public participation, and regulatory constraints. Regarding the second research question, the Court reaffirmed its stance of refraining from intervening in criminal policy matters related to penal norms, further noting the practical reality that many cases in the field are discontinued.